1974
DOI: 10.1159/000114305
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidotic Polyneuritis of Type III (Iowa-Van Allen)

Abstract: The present paper describes a family showing the association of a neuropathy and a nephropathy with a gastropathy, as well as deafness and ocular changes (cataracts and vitreous opacities), which is similar to a family described by Van Allen et al. This provides evidence that a recently described third type of primary amyloidosis is a clinical entity in itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Tourtellotte et al (1963), on the other hand, concluded that the Portuguese and Indiana forms of amyloidosis were likely to be the same disease. The frequency of occurrence of nephropathy in the Iowa type (van Allen et al, 1969;Gimeno et al, 1974) marks it out as distinct, as do the late onset and frequency of cardiac involvement in the Scandinavian and English families of Andersson (1970) and Zalin et al (1974). Even where the clinical manifestations in different families are similar, there is no firm evidence to suggest that the mutations are the same except in the Portuguese and possibly the Japanese forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourtellotte et al (1963), on the other hand, concluded that the Portuguese and Indiana forms of amyloidosis were likely to be the same disease. The frequency of occurrence of nephropathy in the Iowa type (van Allen et al, 1969;Gimeno et al, 1974) marks it out as distinct, as do the late onset and frequency of cardiac involvement in the Scandinavian and English families of Andersson (1970) and Zalin et al (1974). Even where the clinical manifestations in different families are similar, there is no firm evidence to suggest that the mutations are the same except in the Portuguese and possibly the Japanese forms.…”
Section: Discussionmentioning
confidence: 99%
“…However, they overlap. Thus in the Iowa type classified with the hereditary amyloid neuropathies (van Allen et al, 1969;Gimeno et al, 1974), renal involvement was frequent and was the usual cause of death. In the English (Zalin et al, 1974) and Scandinavian (Andersson, 1970) families with neuropathy as the predominant feature, cardiac involvement was a common finding.…”
Section: Discussionmentioning
confidence: 99%